Pancasila Economic System in the Era of Globalization - Shinta Wulandari (Nalar Global Foundation, 2021)
One solution to the various problems faced by the Indonesian people today is to revive the spirit of Pancasila. Pancasila is the essence of Indonesia's existence as a country. Pancasila serves as the basis of the state, ideology, philosophy, and also as the embodiment of the basic principles for an independent Indonesia. Therefore, the revitalization/revival of Pancasila should be the main focus of government programs, so that the values ​​of Pancasila can be inspired by every Indonesian nation. Especially in the case of the Pancasila Economic System, the founders of Indonesia believed that the Pancasila Economic System could free the people from poverty, hunger, social inequality and corruption, besides that it could also be the basis for being able to cooperate with other countries as a whole. This can be realized by uniting determination, action, and integration/merging from various fields and skills to achieve the ideals of prosperity for the entire Indonesian nation.